THE DEVELOPMENT APPLICATION OF PASURUAN LOCAL CULTURE AS MOBILE INTERACTIVE LEARNING MEDIA OF DECORATIVE MATERIAL IN PASURUAN - Putri, Rizki Amalia; Hadayaningrum, Warih (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2020)
The increase use of technology in daily life needs the development of leaning media which utilizes technology as well. The use of mobile phones is increasing among students and the use of inappropriate makes the device as a medium of entertainment. It needs a learning media using mobile phones in the form of applications. There is lack of applications with the theme of education in accordance with learning. Mobile phones are not used as learning media by teachers and students. The reverence of learning material and learning media makes research on technology education need to be raised as a matter of matter in the field. The development of the local cultural application of Pasuruan has become one of the mobile interactive learning media that can be used as a medium for learning revision in and outside the school. The development process is carried out through the 4D stages, which are define, design, develop and dessemine. Based on the results of the research, it can be seen that there is the effectiveness of learning to use learning media applications. In addition, the results of the validator shows decent results as products which can be used. The respond of teacher and student show satisfied result in using Pasuruan local culture application as learning media.